Performance improvements of a VLC system, in a V2X context, using a different multiplexing technique - Anass Kharbouche; Zhour Madini; Younes Zouine (Universitas Ahmad Dahlan, 2023)
This paper scrutinizes visible light communication (VLC) employing hybrid optical time division multiplexing (OTDM) wavelength division multiplexing (WDM). It also demonstrates the simulation of VLC using the direct sequence optical code division multiple access (DS-OCDMA) system developed by OptiSystem-Matlab Co-simulation. The profits of WDM and OTDM capacities have been combined using two levels of freedom to build up of the system. The performances are demonstrated in the simulated findings of the bit error rate (BER) in relationship with the data rate and the number of users. First, the simulated results display the usefulness of the system. Then, the number of users has been significantly enhanced. Besides, the OCDMA functions by appointing a specific code to each user and could provide asynchronous and simultaneous access to numerous users. One drawback is multiple access interference (MAI). The use of very long code sequences is crucial in order to lessen this effect. Hence, very large bandwidths are essential. This study aims at demonstrating, through system simulation, the practicability of an all-optical conventional correlation receiver dedicated to a DS-OCDMA access network link. Again, OptiSystem has been used to realize our blocks.